2021
DOI: 10.1186/s12891-021-04378-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of conservative therapy before and after surgery for carpal tunnel syndrome

Abstract: Background Conservative therapies are typically offered to individuals who experience mild or intermittent symptoms of carpal tunnel syndrome (CTS) or postoperatively to subjects who have undergone carpal tunnel release. Although long-term studies report mostly positive results for carpal tunnel release, knowledge on the need for conservative treatments following surgery is scarce. The aim of this retrospective cohort study was to examine the use of conservative therapies before and after carpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
(36 reference statements)
1
1
0
Order By: Relevance
“…The prevalence of women observed during this review, as well as the subjects’ range age, is in line with the epidemiological studies carried out in the past [ 36 , 37 , 38 , 39 ]. The presence of a higher quantity of women may be due to their prevalence in types of employment prone to suffer from this pathology [ 39 ].…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of women observed during this review, as well as the subjects’ range age, is in line with the epidemiological studies carried out in the past [ 36 , 37 , 38 , 39 ]. The presence of a higher quantity of women may be due to their prevalence in types of employment prone to suffer from this pathology [ 39 ].…”
Section: Discussionsupporting
confidence: 88%
“…Even though there are advantages of the surgical treatment method, it is necessary to take into consideration possible complications of those as well. Therefore, conservative treatment remains the first line for the treatment of mild and moderate CTS (Multanen, J., et al 2021). These facts were motivating for us to examine the degree of the median nerve damage at the moment when our patients report for the first time in order to electrodiagnostically confirm suspicions of CTS and if it is still possible to have the conservative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While non-operative treatment is the primary option, invasive treatment is often necessary. According to a recent study, 77% of patients undergoing median nerve release surgery had previously received some form of non-operative treatment 6. Carpal tunnel release surgery is considered the gold standard and has been shown to give excellent results in 75% of cases 7.…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent study, 77% of patients undergoing median nerve release surgery had previously received some form of nonoperative treatment. 6 Carpal tunnel release surgery is considered the gold standard and has been shown to give excellent results in 75% of cases. 7 Another study found a significant reduction in Symptom Severity Scale for 88% of patients treated.…”
Section: Introduction Backgroundmentioning
confidence: 99%